A Theology of Believer’s Repentance in Habakkuk from a Triadic Interpretative Approach - Marsh, Cory M. (The Evangelical quarterly, 2021)
Because themes surrounding theodicy, prayer, and patience in Habakkuk have traditionally taken the focus of scholars, a theology of personal, believer’s repentance and faith has not been afforded as much attention. Filling the lacuna, this article argues that in addition to the customarily treated themes, Habakkuk also contains a subtle yet powerful theology of repentant-faith for believers in Yahweh. Furthermore, such repentance is not necessarily dependent on the presence of sin or disobedience from which to turn. Following a triadic interpretive method covering history, literature, and theology, the conclusion drawn is that though explicit terms for ‘repentance’ do not appear on the surface of the text, the concept is certainly implied. After receiving Yahweh’s vision in chapter two Habakkuk’s clear change of thinking, or repentance, is evidenced in chapter three resulting in his worshipful prayer and psalm closing out the book. Pivoting from confusion and doubt to reinvigorated faith and reverence toward the God who is trustworthy through the grimmest of circumstances, Habakkuk provides a commanding lesson on the need of continual repentant-faith, or correct thinking, for believers in any age.